Data from various stunning attempts for Nile tilapia (Oreochromis Niloticus) - Sundell, Erika (Swedish University of Agricultural Sciences, 2024)
The study that this data supports aimed to evaluate the stunning effectiveness of various stunning attempts on Nile tilapia by measuring brain activity to assess neurological indicators of conscioussness/unconsciousness. Thus, this data set contains raw data from measurements of brain activity using electroencephalography in Nile tilapia. Data were collected before and after stunning attempts using the following stunning methods: Live chilling, mechanical stunning (percussion), electrical stunning and a combinational approach consisting of electrical stunning followed by direct throat cutting and chilling. The data is extracted from Labchart, where data was collected using a Powerlab and a Bioamp. The data contains the mean amplitude during 20-80 s during the 200 ms long light and dark phases. The data set also contains the mean amplitude during 10 s before short electrical exposure as well as the mean amplitude of the signal during the time that the epileptic-like seizure lasted after electrical exposure (i.e., 9-27 s). The data also include information on the time that visually evoked responses (VERs) were lost after stunning, as well as the induction time (when applicable) for the loss of VERs.

Studien som datan tillhör syftade till att utvärdera bedövningseffekten av olika bedövningsförsök på Niltilapia genom mätningar av hjärnaktivitet för att studera neurologiska indikatorer på medvetande/medvetslöshet. Datasetet innehåller således rådata från mätningar av hjärnaktivitet med hjälp av elektroencefalografi på Nile tilapia. Datan samlades in innan och efter bedövningsförsök med följande bedövningsmetoder: Nedkylning, mekanisk bedövning (perkussion), elektrisk bedövning och en kombinationsbedövning bestående av elektrisk exponering följt av direkt strupskärning och nedkylning. Datan är extraherad från Labchart, där datan, med hjälp av ett Powerlab och en Bioamp samlats in. Datan innehåller dels medelamplituden under 20-80 s under de 200 ms långa ljusa och mörka faserna. Datasetet innehåller också medelamplituden under 10 s innan kort elektriskt exponeringstid samt medelamplituden på signalen under den tid som det epilepsi-liknande anfallet höll i sig efter elexponering (dvs 9-27 s). Datan innehåller också information om tiden som visuellt framkallade responser (VERs) förlorats efter bedövning, samt induktionstiden (när det är applicerbart) för förlorandet av VERs.
Data från olika bedövningsförsök för Niltilapia (Oreochromis Niloticus)
Keywords: Agricultural and aquaculture facilities; Jordbruks- och vattenbruksanläggningar; electroencephalography; oreochromis niloticus (linnaeus, 1758); consciousness; medvetande; Grand mal; Anfall; unconsciousness; medvetslös; nile tilapia; niltilapia; Live chilling; Nedkylning; Electrical stunning; Elektrisk bedövning; Stunning; Bedövning; Percussive stunning; Mekanisk bedövning; Visually evoked responses; Visuellt framkallade responser; Brain activity; Hjärnaktivitet; Zoology; Zoologi; Behavioural Sciences Biology; Etologi; Fish and Aquacultural Science; Fisk- och akvakulturforskning